Fermentasi Nira Nipah Menjadi Asam Asetat Menggunakan Acetobacter Pasteurianus Dengan Variasi Konsentrasi Gula Dan Waktu Fermentasi - Rohaya, Rohaya; Chairul, Chairul; Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Acetic acid is widely used in the manufacture of chemicals, food additives, and cosmetics. Acetic acid can be produced by fermentation using nypa sap raw material because it contains sucrose, glucose, and fructose. One of the factors that influence fermentation results is the concentration of sugar. The fermentation process was carried out with two fermentation stages in stage I using S. Cerevisiae at 1,3 and 5 days fermentation time with a sugar concentration of 249 g / L. The resulting bioethanol was followed by the second stage of fermentation using A.Pasteurianus at 1, 3, 5, 7 and 9 days fermentation time. The maximum concentration of acetic acid was obtained at 9 days fermentation and bioethanol substrate 23,68 g / L which was 5,35 g / L and 49,73% yield.Keywords : Acetic acid, A. Pasteurianus, fermentation, nypa sap.